2014
DOI: 10.1245/s10434-014-3612-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Preoperative Inspiratory Muscle Training Programs to Prevent Pulmonary Complications in Patients Undergoing Esophagectomy: A Randomized Controlled Pilot Study

Abstract: Preoperative IMT-HI showed to be a promising, effective, and feasible intervention to reduce PPCs in EC patients undergoing esophagectomy. Further research with a larger sample size is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 21 publications
6
93
1
3
Order By: Relevance
“…This is in line with earlier studies that show that IMT can improve inspiratory muscle strength and endurance after 2 weeks of training in patients undergoing major invasive surgery [16,38,39]. Baseline values and the average increase of 20% of MIP-max are also comparable to the results in these studies.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with earlier studies that show that IMT can improve inspiratory muscle strength and endurance after 2 weeks of training in patients undergoing major invasive surgery [16,38,39]. Baseline values and the average increase of 20% of MIP-max are also comparable to the results in these studies.…”
Section: Discussionsupporting
confidence: 92%
“…Systematic reviews of patients undergoing cardiac and upper abdominal surgery have shown that preoperative IMT can decrease the rate of postoperative pneumonia. Whether preoperative IMT is of benefit in patients undergoing oesophagectomy is unclear. The aim of this RCT was to assess the effect of a preoperative IMT programme on the rate of postoperative pneumonia in patients undergoing oesophagectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary complications can be reduced by minimally invasive surgery, thoracic epidural analgesia, and early enteral nutrition . Other strategies to improve preoperative condition of the patient include physical therapy to increase cardiorespiratory function . A systematic review including 12 studies evaluating the effects of preoperative exercise therapy on postoperative complication rate and length of hospital stay concluded that preoperative exercise therapy can be effective for reducing postoperative complication rates and length of hospital stay after cardiac or abdominal surgery .…”
Section: Patient Selection For Surgerymentioning
confidence: 99%